Enzymatic synthesis of 1,3-dicaproyglycerol by esterification of glycerol with capric acid in a organic solvent system - Sanchez, Daniel Alberto (2013)
In this work, the esterification of glycerol with capric acid catalyzed by an immobilized form of a 1,3-positionally selective lipase (Rhizomucor miehei) showed to be effective for the synthesis of 1,3-dicaprinin n-heptane as the reaction medium.The effects of the reaction parameters were studied using an experimental factorial design of threefactors and three levels with two central points. The selected experimental variables were amount ofglycerol adsorbed on silica gel (G), biocatalyst load (E) and reaction temperature (T), and the responsevariables were total conversion of capric acid, acylglycerol fractions, selectivity and yield of dicaprin, andacyl migration reaction. The range of each parameter was selected as follows: G = 50-250 mg, E = 20-40 mgand T = 40-60 ◦C. At optimum conditions 73% capric acid conversion was achieved, with 76% dicaprinselectivity, and selectivity to the specific 1,3-dicaprin of 70% of total products. An adequate selectionof the reaction conditions is necessary not only to maximize the conversion of capric acid, but also tominimize the acyl migration reaction and the generation of undesired products. Evidence of kineticallycontrolled enzymatic acyl migration from sn-3/sn-1 to sn-2 is presented.